Differentiating Phenotypes of Coronavirus Disease-2019 Pneumonia by Electric Impedance Tomography - Lovas, András; Chen, Rongqing; Molnár, Tamás; Benyó, Balázs; Szlávecz, Ákos; Hawchar, Fatime; Krüger-Ziolek, Sabine; Möller, Knut (Frontiers in Medicine, 2022)
Introduction: Coronavirus disease-19 (COVID-19) pneumonia has different phenotypes. Selecting the patient individualized and optimal respirator settings for the ventilated patient is a challenging process. Electric impedance tomography (EIT) is a real time, radiation-free functional imaging technique which can aid the clinicians in differentiating the “low” (L-) and “high” (H-) phenotypes of COVID-19 pneumonia described previously. Methods: Two patients (‘A’ & ‘B’) underwent a stepwise positive end-expiratory pressure (PEEP) recruitment by 3 cmH2O of steps from PEEP 10 to 25 and back to 10 cmH2O during a pressure control ventilation of 15 cmH2O. Recruitment manoeuvres were performed under continuous EIT recording on a daily basis until patients required controlled ventilation mode. Results: Patient ‘A’ and ‘B’ had a 7 and a 12 day long trial respectively. At the daily baseline patient ‘A’ had a significantly higher compliance: mean±SD=53±7 vs. 38±5 ml/cmH2O (P<0.001) and a significantly higher physiological dead space according to the Bohr-Enghoff equation than patient ‘B’: mean±SD=52±4 vs. 45±6% (P=0.018). Following recruitment manoeuvres patient ‘A’ had significantly higher cumulative collapse ratio detected by EIT than patient ‘B’: mean±SD=0.40±0.08 vs. 0.29±0.08 (P=0.007). For patient ‘A’ cumulative collapse ratio at the end of the recruitment manoeuvres significantly deteriorated (R2=0.824, P=0.005) by moving forward in days, while not for patient ‘B’ (R2=0.329, P=0.5). Conclusions: Patient “B” was recognized as H-phenotype with high elastance, low compliance, higher recruitability and low ventilation-to-perfusion ratio, meanwhile patient ‘A’ was identified as an L-phenotype with low elastance, high compliance and lower recruitability. Observation by EIT was not just able to differentiate the two phenotypes but it even could follow the transition from L- to H-type with patient ‘A’.